Slow Tourism - Sutthitep, Juthathip (Journal of Thai Hospitality and Tourism, 2016)
The principles of slow tourism can be exploited so that goods and services can be better developed. In order to help the service owners to correctly identify and serve the specific needs of tourists. If this process is effectively administered, slow tourism can become sustainable, and its sustainability can inevitably affect the well-being of all people whose lives are related to slow tourism. A proper amount of time should be allotted for the tourists to accomplish the following: 1) to absorb the elements of the environment and 2) to learn to appreciate the local ways of life, the local history & culture, and the beauty of the tourist areas. Because appreciation is not simply fostered by simply reading a sign or by seeing a poster on the wall, activities in the slow tourism areas should encourage tourists to use all five of their senses. Therefore, those individuals, who are engaging in the development of slow tourism should pay close attention to the following principles for successful slow tourism which are: 1) Sustainability, 2) Learning about Local, 3) Organic, 4) Wellness, 5) Time, 6) Opportunity,7) Understanding, 8) Responsibility, 9) Appreciation, 10) Satisfaction, and 11) Movement.